2017
DOI: 10.1021/acsami.7b14942
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Analysis on a Single Porous Hydrogel Bead with Encoded SERS Nanotags

Abstract: Bead-based assays have drawn more and more attention in biomedical fields. Herein, we proposed a novel approach to achieve multiplex analysis on a single porous hydrogel bead (PHB) with Raman dyes (RDs) encoded core-shell surface-enhanced Raman scattering (SERS) nanotags. Because of the amplified signal of RDs by core-shell metal structure of the nanotag and the high surface area to volume ratio (SVR) of the PHB, the sensitivity and linear dynamic range (LDR) of the as-proposed multiplex analysis method are si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…2019, 31, 1801159 Figure 7. [73] By simply altering the diameters of the assembled nanoparticles, multicolor beads, with different characteristic reflection peaks were prepared for multiplex encoding. a,b) Schematic illustration of the self-barcode particles, with opal structure (a) and inverse-opal structures (b).…”
Section: Circulating Tumor Cells (Ctcs) or Exosomes Contain Firsthandmentioning
confidence: 99%
“…2019, 31, 1801159 Figure 7. [73] By simply altering the diameters of the assembled nanoparticles, multicolor beads, with different characteristic reflection peaks were prepared for multiplex encoding. a,b) Schematic illustration of the self-barcode particles, with opal structure (a) and inverse-opal structures (b).…”
Section: Circulating Tumor Cells (Ctcs) or Exosomes Contain Firsthandmentioning
confidence: 99%
“…Recently, as an emerging eld, the photonic-plasmonic hybrid structure has drawn extensive attention in the SES study. [26][27][28][29][30][31][32][33][34][35] The hybrid structure works as an optoplasmonic system to simultaneously benet from high Q-factors of a photonic structure, as well as small modal volumes and extreme near-eld enhancements of a plasmonic structure, 36 which will be helpful to improve the enhancement ability, practicality, and versatility of an SES substrate. For example, Ahn et al demonstrated enhanced uorescence of dye molecules within a designed photonic-plasmonic structure constructed by putting a microsphere exactly into a plasmonic cavity.…”
Section: Introductionmentioning
confidence: 99%
“…32 Liu et al proposed a photonic-plasmonic hybrid structure constructed with an inverse three-dimensional photonic crystal and Au nanoparticles, and demonstrated its SERS application for the multi-objective detection of biomolecules. 33 Despite these achievements, there are still some challenges in the SES study based on photonic-plasmonic hybrid structures, which need urgent action. For example, the mechanism of SES in the optoplasmonic system is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…One main approach to improving the efficiency of such materials is the addition of nanoparticles to the titanium surface, which can trap electrons and lessen the recombination of electron-hole pairs [16,17]. TiO 2 modified with Ag has been proven to restrain the recombination of photo-excited electrons and holes, which can improve the photocatalytic performance [18]. In our recent work, nanocap arrays of TiO 2 /Ag and co-sputtering TiO 2 -Ag were fabricated on two-dimensional colloidal arrays [19].…”
Section: Introductionmentioning
confidence: 99%